Immunocytochemical Localization of the Kinetochore Protein Nuf2p on the Gametophyte Chromosomes of a Cultivar of Saccharina (Phaeophyta) - Dong, Wu-Shan; Liu, Peng-Fei; Liu, Yu; Du, Yu; Bi, Yan-Hui; Zhou, Zhi-Gang (Frontiers in Marine Science, 2020)
Nuclear filament-containing protein 2 (Nuf2p), a centromere-associated protein, is an indispensable component of Ndc80 complex, which is important for stable microtubule–kinetochore attachment, chromosome pairing, and spindle assembly in mitosis. Based upon contig sequences coding for Nuf2p from a pyrosequencing transcriptome of Saccharina japonica, primers were designed for molecular cloning of this kinetochore protein. The open reading frame (ORF) of this gene SjNuf2 was 1,452 bp long, encoding a putative protein consisting of 483 amino acids. Multi-sequence alignment showed SjNuf2p possessed several conserved domains of Nuf2, Spc7, SPT2, and MIT. To illustrate the location of SjNuf2p using immunocytochemistry, its ORF was inserted into a prokaryotic expression vector pET-28a. Then, the recombinant SjNuf2p (rSjNuf2p) was induced to be expressed in Escherichia coli. The rSjNuf2p was verified by Western blotting with the commercial anti-6 × His-tag antibody and then purified using affinity chromatography. The polyclonal antibody of anti-SjNuf2p was raised against the purified rSjNuf2p. Western blotting with this prepared antibody showed the presence of SjNuf2p in the gametophytes of a Saccharina cultivar. SjNuf2p and α/β-tubulin were subsequently co-localized to the paraffin sections of kelp chromosomes with their corresponding antibodies, thus illustrating that SjNuf2p could reside at the kelp centromeres. This study laid a solid foundation for kelp centromere and karyotype analyses.